Processing and Packaging Healthy Food for Pregnant Women, Newborns and Toddlers at the North Cimahi Community Health Center - Marini, Sri; Sanjaya, Sonny; Wibawa, Idham Sakti; Fajri, Ilham; Devi, Ghini Kunthala (Universitas INABA, 2024)
Pregnant women, toddlers and toddlers are at risk of giving birth to babies with low birth weight and stunting. Nutrition problems in Indonesia are currently emerging as complex problems. Chronic malnutrition conditions such as stunting are one of them. Health services should empower cadres in health promotion to prevent stunting by processing food menus and packaging according to local wisdom which is easily available in the area. AKPAR NHI Bandung, in this case a university in the field of hospitality and tourism, is a partner of the Cipageran Community Health Center, North Cimahi district. The situation analysis in this community partnership program focuses on education on healthy food processing and at the same time packaging food for pregnant women, children and Toddlers. This community service proposal is proposed with a theme